(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Modern digital technologies, including 3D scanning and 3D printing, play a key role in improving the design and manufacturing processes of temporary prosthetics in dental implantology. These technologies have significantly increased the precision of prosthesis fabrication, accelerated production times, and enhanced aesthetic qualities, which in turn improves the patients’ quality of life by minimizing discomfort and reducing recovery time after implant placement. The article reviews recent advancements in digital design and manufacturing of temporary prosthetics, as well as their impact on clinical outcomes.